2018
DOI: 10.1093/brain/awy190
|View full text |Cite
|
Sign up to set email alerts
|

NEGR1 and FGFR2 cooperatively regulate cortical development and core behaviours related to autism disorders in mice

Abstract: See Contreras and Hippenmeyer (doi:) for a scientific commentary on this article.Autism spectrum disorders (ASDs) are complex conditions with diverse aetiologies. Szczurkowska et al. demonstrate that two ASD-related molecules – FGFR2 and Negr1 – physically interact to act on the same downstream pathway, and regulate cortical development and ASD-relevant behaviours in mice. Identifying common mechanisms in ASDs may reveal targets for pharmacological intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 140 publications
(195 reference statements)
2
76
0
Order By: Relevance
“…Conversely, some other models, (i.e., Pcdh19 X LacZ /Y; (Lim et al 2019)) did not show gross brain developmental abnormalities, but they did show some ASD-related behavioral phenotypes (Table 1). We found here that in rats electroporated with shRNA-Pcdh19 in the somatosensory cortex, brain developmental abnormalities were accompanied by decreased vocalisation and huddling behaviour in young pups, and poor sociability in adult animals, as already shown in animal models of ASD (Wöhr and Scattoni 2013;Scattoni, Crawley, and Ricceri 2009;Ferhat et al 2016;Szczurkowska et al 2018;Naskar et al 2019). Interestingly, also a large number (32%) of people with EIEE9 carry a diagnosis of ASD (Smith et al 2018;Clarke 2015)) with social deficits early in life that persist and may become more prominent in adulthood (Depienne et al 2011).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Conversely, some other models, (i.e., Pcdh19 X LacZ /Y; (Lim et al 2019)) did not show gross brain developmental abnormalities, but they did show some ASD-related behavioral phenotypes (Table 1). We found here that in rats electroporated with shRNA-Pcdh19 in the somatosensory cortex, brain developmental abnormalities were accompanied by decreased vocalisation and huddling behaviour in young pups, and poor sociability in adult animals, as already shown in animal models of ASD (Wöhr and Scattoni 2013;Scattoni, Crawley, and Ricceri 2009;Ferhat et al 2016;Szczurkowska et al 2018;Naskar et al 2019). Interestingly, also a large number (32%) of people with EIEE9 carry a diagnosis of ASD (Smith et al 2018;Clarke 2015)) with social deficits early in life that persist and may become more prominent in adulthood (Depienne et al 2011).…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, around 32% of people with EIEE9 fulfill the criteria for ASD, including sensory alterations (Smith et al 2018). Recently, we have demonstrated that downregulation in the upper layer of the somatosensory cortex of another cell-adhesion molecule (Negr1) with a similar pattern of expression as Pcdh19 and also associated to human ASD (Szczurkowska et al 2018), resulted in migration defects and core symptoms related to ASD (along with sensory alterations) in rodents (Szczurkowska et al 2018). Thus, we decided to investigate whether Pcdh19 downregulation by a short harpin RNA (shRNA) strategy (Bassani et al 2018) in the somatosensory cortex resulted in migration defects and ASD-related behaviors.…”
Section: Pcdh19 Expression Is Temporally and Spatially Regulated In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct control by Negr1 of synapse number and neurite outgrowth was also demonstrated in an in utero study [27]. When negr1 expression was silenced in mouse embryonic brain at E15.5 by in utero electroporation, dendritic length and number of neurite processes of layer II/III cortical neurons at P7 decreased significantly compared with their controls [27]. These results confirm that Negr1 deficiency prevents normal morphological development of pyramidal neurons in vivo.…”
Section: Role Of Negr1 In Neuronal Synaptogenesis and Neu-rite Outgrowthsupporting
confidence: 62%
“…Taken together, these results indicate that Negr1 is an important regulator of not only synapse number, but also of maturation of dendritic processes; moreover, its regulatory effects are dependent on the developing stages of neurons. Direct control by Negr1 of synapse number and neurite outgrowth was also demonstrated in an in utero study [27]. When negr1 expression was silenced in mouse embryonic brain at E15.5 by in utero electroporation, dendritic length and number of neurite processes of layer II/III cortical neurons at P7 decreased significantly compared with their controls [27].…”
Section: Role Of Negr1 In Neuronal Synaptogenesis and Neu-rite Outgrowthmentioning
confidence: 72%